A rule-based decision support system for real estate brokerage service evaluation - Ferreira, F.; Spahr, R.; Sunderman, M.; Banaitis, A.; Ferreira, J. (BAI 2016 Proceedings of the International Conference on International Conference on Business and Information, 2016)
Real estate brokers or realtors are expected to possess superior knowledge of their local markets, and typically require commissions in return for their services. The evaluation of their performance is an important issue in justifying their commissions. We develop a learning-oriented decision-making process for evaluating real estate brokerage services, which concentrates on understanding the nature, the role and the interaction of the evaluation aspects of real estate brokerage service quality by integrating cognitive maps and the Decision EXpert (DEX) approach. Results suggest that this framework permits new rudiments to be considered in the realtor decision-making and sales process, facilitating transparency and understanding of realtor functions that may lead to recommendations to improve the performance and quality of these functions. Avenues for future research are also presented.